ANALYSIS OF MICROBIAL CLINICAL ISOLATES AND ANTIBIOTIC SUSCEPTIBILITY PATTERNS IN DIABETIC PATIENTS. - Khwela, Nkosinathi; Thembane, Nokukhanya; Nsele, Nhlanhla Wiseman (Student’s Journal of Health Research Africa, 2023)
Introduction: Diabetes mellitus is a chronic metabolic disorder characterized by high blood glucose levels resulting from insulin deficiency or impaired insulin action. Diabetic patients are more susceptible to microbial infections due to compromised immunity and impaired wound healing. Understanding the types and antibiotic susceptibility patterns of microbial clinical isolates in diabetic patients is crucial for effective management and prevention of complications. However, there is a knowledge gap regarding the prevalence of specific pathogens and their antibiotic susceptibility patterns in diabetic patients, particularly in KwaZulu Natal, South Africa. This study aimed to identify the types of microbial clinical isolates commonly found in diabetic patients and assess their antibiotic susceptibility patterns. Methodology: A retrospective cross-sectional study was conducted at Inkosi Albert Luthuli Central Hospital in KwaZulu Natal, involving 100 diabetic patients. Microbiological analysis and antibiotic susceptibility testing were performed using standard methods. The types and frequencies of microbial isolates were determined, and their antibiotic susceptibility patterns were evaluated. Results: Enterococcus faecalis, Klebsiella species, methicillin-resistant Staphylococcus aureus (MRSA), and Pseudomonas aeruginosa were among the commonly identified microbial isolates. The antibiotic susceptibility patterns varied among the isolates, highlighting the importance of targeted treatment selection. Conclusion: This study contributes to bridging the knowledge gap and provides valuable insights for the management of infections in diabetic patients. The findings can guide the selection of appropriate antibiotics, inform infection prevention strategies, and ultimately improve patient outcomes in this vulnerable population.